Report on the meeting dedicated to the 47th anniversary of the October Revolution in Moscow, November 6, 1964 - Brezjnev, Leonid Iljitsj (Moscow : Novosti, 1964)
Bibliotheek Camille Huysmans
Themanummer van: 'The Daily Review : translations from the Soviet press'
Engels
Brochure
Keywords: Sovjet-Unie.